Accumulation of pesticides in pacific chorus frogs (Pseudacris regilla) from California's Sierra Nevada Mountains, USA. (26th July 2013) - Smalling, Kelly L.; Fellers, Gary M.; Kleeman, Patrick M.; Kuivila, Kathryn M.
Abstract: Pesticides are receiving increasing attention as potential causes of amphibian declines, acting singly or in combination with other stressors, but limited information is available on the accumulation of current‐use pesticides in tissue. The authors examined potential exposure and accumulation of currently used pesticides in pond‐breeding frogs ( Pseudacris regilla ) collected from 7 high elevations sites in northern California. All sites sampled are located downwind of California's highly agricultural Central Valley and receive inputs of pesticides through precipitation and/or dry deposition. Whole frog tissue, water, and sediment were analyzed for more than 90 current‐use pesticides and pesticide degradates using gas chromatography–mass spectrometry. Two fungicides, pyraclostrobin and tebuconazole, and one herbicide, simazine, were the most frequently detected pesticides in tissue samples. Median pesticide concentration ranged from 13 µg/kg to 235 µg/kg wet weight. Tebuconazole and pyraclostrobin were the only 2 compounds observed frequently in frog tissue and sediment. Significant spatial differences in tissue concentration were observed, which corresponded to pesticide use in the upwind counties. Data generated indicated that amphibians residing in remote locations are exposed to and capable of accumulating current‐use pesticides. A comparison of P. regilla tissue concentrations with water and sediment data indicated that the frogs are accumulating pesticides and are potentially a more reliable indicator of exposure to this group of pesticides than either water or sediment. Environ Toxicol Chem 2013;32:2026–2034. © 2013 SETAC